Antioxidant and antimicrobial properties of zinc oxide nanoparticles green synthesized with Bunium persicum essential oil - Neda Akhtari; Elham Mahdian; Fatemeh Oroojalian; Vahid Hakimzadeh (Scientific Reports)
Abstract This study evaluated the antioxidant and antibacterial properties of zinc oxide nanoparticles containing Bunium persicum (Boiss.) B. Fedtsch. essential oil synthesized using a green method. The analyses were conducted with three replications using a completely randomized methodology. The means were compared using Duncan’s multiple range test at a significance level of 5% using SPSS version 22 statistical software. In the microbial test, the antimicrobial property of zinc oxide nanoparticles with cumin essential oil was significantly higher than that of B. persicum (Boiss.) B. Fedtsch. essential oil in both disc diffusion and microbroth dilution methods (p < 0.05). In addition, zinc oxide nanoparticles with B. persicum (Boiss.) B. Fedtsch. essential oil had the most significant effect on Candida Albicans yeast, then on the gram-positive Staphylococcus aureus bacteria, and finally on the gram-negative Escherichia coli bacteria. Zinc oxide nanoparticles combined with B. persicum (Boiss.) B. Fedtsch. essential oil showed a better result than B. persicum (Boiss.) B. Fedtsch. essential oil in measuring the amount of total phenolic compounds (p < 0.05). In the test of particle size and dispersion index, there was a significant difference in the samples (p < 0.05). The lowest particle size and particle size dispersion index were related to the sample of zinc oxide nanoparticles with B. persicum (Boiss.) B. Fedtsch. essential oil.